Fostering Entrepreneurial Spirit: The Impact of the 'Kantin Kejujuran' Program on OSIS Members in SMP YBPK Kota Kediri - Machful Indrakurniawan; Mahardika Darmawan Kusuma Wardana; Ria Wulandari (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents the results and implications of the "Kantin Kejujuran" community engagement program, aimed at cultivating entrepreneurial values among members of the Student Intra-School Organization (OSIS) in SMP YBPK Kota Kediri. The study utilized a three-stage methodological approach, beginning with the creation of a workplan to ensure the program's smooth execution without disrupting regular school activities. Subsequently, the program included a seminar on entrepreneurship specifically designed for OSIS members. Finally, a monitoring and evaluation process was conducted to assess the program's effectiveness. The results demonstrate a significant improvement in the entrepreneurship capabilities of OSIS members, as indicated by pretest and posttest data. Through practical involvement in the "Kantin Kejujuran," students engaged in activities such as planning, inventory management, and customer interaction, fostering their entrepreneurial skills, risk-taking, creativity, innovation, leadership, and responsibility. The program emphasized the importance of ethical conduct and social responsibility in business, offering students the opportunity to run a business with principles of honesty, fairness, and transparency. Beyond honing entrepreneurial skills, the program also enhanced students' independence, self-confidence, and interpersonal abilities. Encountering decision-making processes, challenges, and learning from mistakes promoted a positive attitude towards failure and resilience. Overall, this article highlights the effectiveness of the "Kantin Kejujuran" program in nurturing entrepreneurial spirit among OSIS members, with implications for educators and policymakers seeking to foster entrepreneurial development in schools worldwide. Highlight: Significant impact on OSIS members: The "Kantin Kejujuran" program effectively fosters entrepreneurial spirit among OSIS members at SMP YBPK Kota Kediri, demonstrated by significant improvements in their entrepreneurship capabilities from pretest to posttest. Practical business learning: Through the kiosk, students engage in practical business management, learning essential skills such as planning, inventory management, and customer interaction, while also developing qualities like risk-taking, creativity, innovation, leadership, and responsibility. Fostering positive attitudes: The program not only enhances entrepreneurial skills but also promotes positive attitudes towards failure, resilience, and decision-making, providing students with the confidence and independence to pursue their business ideas in the future. Keyword: Honesty Canteen, Entrepreneurship, Business Management, Honesty Values, Junior High School Students